Transitions in poverty and its deprivations: an analysis of multidimensional poverty dynamics - Suppa, N (Springer Berlin Heidelberg, 2018)
This paper explores a novel way to analyse poverty dynamics that is specific to certain measures of multidimensional poverty, such as the adjusted headcount ratio" of the Alkire-Foster class of measures. Assuming there is panel data available, I show that a simultaneous and comprehensive account of transitions in deprivations and poverty allows complex interdependencies between dimensions in a dynamic context to be handled and, at the same time, allows for several advanced types of analyses. These analyses include (i) a decomposition of changes in multidimensional poverty, which reveals why poverty decreases or increases; (ii) a framework to examine and understand the relationship between the dashboard approach and dimensional contributions and multidimensional poverty in a dynamic setting; (iii) a presentation of methods that illuminate the process of the accumulation of deprivations.The suggested types of analyses are illustrated using German panel data. Implications for monitoring and policy evaluation are discussed.